2020
DOI: 10.25115/kasp.v1i4.4380
|View full text |Cite
|
Sign up to set email alerts
|

Valoración Del Programa De Educación Emocional Para Docentes (Mademo)

Abstract: La literatura señala que educar en emociones conduce a una mejora en la convivencia, la salud mental y el bienestar, no solo de los alumnos, sino también de los docentes, que cuentan con más recursos para hacer frente a las diferentes exigencias profesionales y el consiguiente desgaste psicológico. Dado los beneficios de la educación emocional para toda la comunidad escolar, se ha desarrollado e implementado el Programa de Educación Emocional para Docentes (MADEMO), basado en el modelo de inteligencia emociona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
36

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(49 citation statements)
references
References 30 publications
3
10
0
36
Order By: Relevance
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
“…The emotional intelligence of teachers must be addressed through the implementation of emotional education programs that take into account the sociodemographic and career variables of the participants. [ 23 , 24 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional intelligence is the ability to perceive, use, express and regulate one’s own emotions as well as those of others by processing emotional information [ 2 ]. Offering education in emotions is a strategy which the education system aims to implement in order to achieve the general well-being of both students and teachers alike [ 3 , 4 ]. International organisations underpin the key role played by emotional intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing emotional education should form part of teachers’ psycho-educational training so that they can address their own emotions and then provide emotion-related education to their students [ 7 , 15 ]. The few programmes that have been geared towards teachers have shown that educators who display high levels of emotional intelligence are able to respond to the demands of their profession and to apply strategies which counter the emotional distress they experience during their careers [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%